Фактор системности в лексике как инструмент лексикографической деятельности (на примере Словаря русского языка ХIХ века) - Kalinovskaia, Valentina; Starovoitova, Ol’ga (Wiener Slawistischer Almanach, 2023)
The diversity of nineteenth-century Russian lexis means that we cannot consider the problem of its description solved. The differential principle of the new historical dictionary of nineteenth-century Russian makes necessary the selection of material which requires the use of new methods in lexicographic practice. The main goal may be considered to be a significant enrichment of the lexical corpus through the use of new data. The analysis of the lexical innovations thus identified has made it possible to establish the main dynamic tendencies in nineteenth-century lexis and to carry out a targeted search for units, using the methods of linguistic forecasting and computer technologies. The compilation of the empirical base of the historical differential dictionary has made it possible not only to record the fact of systemic restructuring within the lexical corpus of nineteenth-century Russian, but also to reveal the potential of certain word bases as new “centers” of word-formation activity.